2012 ACR Classification Criteria and Preliminary Guidelines for Sjögren's Syndrome - Buckley, Rita (MD Conference Express, 2012)
Several facts underpin the impetus to develop classification criteria for Sjögren's syndrome (SS). These include the association of serious adverse events and comorbidities associated with the emergence of biologic therapies as potential treatments for SS, the need for further research to investigate the etiology and genetics of SS, and improved, specific classification criteria that can be effectively used for clinical therapeutic trials.